Optimum design and experimental study of multiple tuned mass dampers with limited stroke. - Lin, Chi-Chang (Earthquake engineering & structural dynamics.)
This paper develops a two-stage optimum design procedure for multiple tuned mass dampers (MTMD) to reduce structural dynamic responses with the limitation of MTMD's stroke. A new performance index, which is a linear combination of structural response ratio and MTMD stroke ratio by a weighting factor α, is proposed; α is in the range from 0 to 1.0. The larger the α, the more important the stroke. The case of α=1.0 indicates that MTMD is locked. The analytical results show that the MTMD's stroke can be significantly suppressed with little sacrifice of structural control effectiveness when an appropriate α is selected. To verify the design algorithm, a 360 kg-MTMD composed of five TMD units arranged in parallel was fabricated. Shaking table tests of a large-scale three-story building with and without the MTMD under earthquake excitations were conducted at the National Center for Research on Earthquake Engineering (NCREE) in Taiwan. The experimental results show that MTMD is not only effective in mitigating the building responses but also is successful in suppressing its stroke.